International and Comparative Employment Relations - Giles, Anthony (Relations industrielles / Industrial Relations, 1999)
The article reviews the book, "International and Comparative Employment Relations," edited by Greg J. Bamber and Russell D. Lansbury.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; Labor relations; Manycountries; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z